POLA DIFRAKSI SINAR X DAN SPEKTRA INFRAMERAH EGGSHELLDERIVED HYDROXYAPATITE (EHA) DIBANDINGKAN DENGAN BEBERAPA SENYAWA KALSIUM FOSFAT - , FAZLUR RACHMAN NAF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bone has an important role in many mechanical and metabolic functions in the body. Although it has an excellent ability to regenerate, when there is a critical defect, bone is not able to regenerate easily. In this condition, bone graft is essential to accelerate regeneration process. Eggshell as one of the natural minerals which are cheap, easily found, and has high calcium content is a potential resource to be processed to result bone graft. The aim of this study was to investigate the characteristics of EHA based on X-ray diffraction pattern and Fourie-transformed infrared spectra and its comparison to some calcium phosphate compounds. Hydroxyapatite was synthesized from eggshell via calcination process in 900 Result of this study indicates that hydroxyapatite was successfully synthesized from eggshell, shown by a good agreement with JCPDS (09-432) in the X-ray diffraction pattern. Compared to HA and CHA, EHA was found to have the lowest crystallinity, identified by broad and diffused peaks on its X-ray diffraction pattern. Infrared spectra of EHA showed some bands indicating POoC, mixed with diammonium hydrogen phosphate solution in 70oâ 90oC as a sequence. White powder produced was characterized using XRD and FT-IR. The X-ray diffraction pattern and infrared spectra were then analyzed descriptively and compared with HA, CHA and DCPD.43-,CO32-, OH- groups and H2O molecules. Similar spectra were also found in HA and CHA, but not in DCPD.